Analysis of Agile Implementation in the Financial Sector - Gonçalo Tato Macias Ferreira (2024)
An increasing need on organizations, specifically in the financial services sector (banking and insurance), to be able to respond quickly to changes and needs in dynamic environments, calls for an implementation of agility-oriented methodologies, ensuring faster and more agile delivery. This dissertation leverages the power of a simplified Systematic Literature Review to investigate what the literature presents regarding this topic. Contextually speaking, a project at Deloitte is used as a basis to study the impact of agile implementation in a European insurance company. Stakeholders from this project were interviewed, as to get a grasp on what professionals in the IT consulting business have worked with, from experience, regarding implementing Agile at large financial services organizations. These interviews were then analyzed and cross-checked with the literature to find convergencies and divergencies. The implementation proved (it is still going on to this day) successful, and the feedback from the interviews corroborated what was studied through the literature, allowing to make conclusions over the positive impact of agility-based methodologies in organizations of this nature.